PEMANFAATAN BEBERAPA BAHAN PELAPIS PADA UREA TERHADAP NITROGEN TERSEDIA DAN SIFAT KIMIA DI VERTISOL PASURUAN - Muhammad Salman; Retno Suntari (Jurnal Tanah dan Sumberdaya Lahan, 2023)
Vertisols have a comparatively low total N content till they are needed, so they need extra external fertilizers within the sort of fertilizers. The coating is one methodology for making fertilizer within the sort of slow-release. The aim of this study was to analyze the impact of zeolite, sago, a mixture of chitosan, and potato flour as a coating for urea fertilizer on the provision of available N and also the chemical properties of Vertisols Pasuruan. This study used a completely randomized design (CRD) with 6 treatments consisted of K (no coating), P1 (zeolite 10%), P2 (sago 2%), P3 (chitosan 3% : potato starch 8%), P4 (zeolite 20%), P5 (sago 4%) and P6 (chitosan 6% : potato starch 6%) with 3 replicates. The results showed that the application of several coating materials on urea had a significant effect on the rate of nitrogen release in the form of ammonium and nitrate from week 1 to week 4. P6 (chitosan 6%: potato starch 6%) treatment showed the lowest results in the release rate of ammonium by 12.517 ppm, which was categorized as high and nitrate by 3.005 ppm, which was categorized as low. The urea coating treatment resulted in lower ammonium and nitrate than the uncoated treatment. The application of several coating materials on urea had a significant effect on the pH value of the soil and cation exchange capacity (CEC). The P6 treatment showed the highest result on the soil pH of 5.363 and CEC values of 41.878 me 100 g-1.